Effect of Feeding Distillers Dried Grains with Solubles (DDGS), and Legume Non-Legume Roughage on Growth Rate and Haematological Profile of Crossbred Heifers - Dhami, Arjan J.; Patel, Dhaval N.; Pathan, Mohsinkhan M.; Shah, Shailesh V.; Lunagariya, Pravinchandra M. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was undertaken on HF x K heifers (n=24) to evaluate the effect of feeding distillers dried grains with soluble (DDGS) and Soy DOC alone or in combination with cereal and/or legume straws as TMR from average 8 months till 19 months of age on their growth, health and haematological profile. Heifers were uniformly distributed into six treatment groups and were fed concentrate and roughage 50-50 ratio. They were offered three different types of concentrates containing 0, 20 and 40% rice DDGS, each half with wheat straw (25%) and another half as a mixture of wheat straw and groundnut gotar. Heifers were also offered green hybrid Napier @ 2 kg/h/d up to 100 kg BW and 4 kg/h/d for above 100 kg BW and Amul’s Chelated Mineral Mixture @ 35 g/animal/d. The protein requirement was met as per the ICAR (2013) feeding standard. Heifers were offered measured extra wheat straw if no leftover was observed from next day. Higher body weight gain (BWG) was observed in 40% DDGS and legume straw fed groups as compared to 40% soy DOC and cereal straw fed groups. The average Hb, PCV and MCHC were significantly (p
Keywords: Crossbred heifers; Distillers dried grains with solubles (DDGS); Growth performance; Haematology; Legume-nonlegume roughage; Soy DOC